IDENTIFIKASI BAKTERI PADA AIR BEKAS CUCIAN PEDAGANG NASI GORENG: Identification of Bacteria in the Wash Water of Fried Rice Vendors - mukarromah, maqiyatul (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2025)
This study aims to identify the types of bacteria present in the wash water used by fried rice vendors and the factors influencing their growth. The research method employed is descriptive qualitative, using selective media analysis with Salmonella Shigella Agar (SSA) and Eosin Methylene Blue Agar (EMB). Samples of the wash water were collected from a fried rice vendor in Ketapang Village, Kalipuro, and analyzed at the Regional Health Laboratory (UPTD Laboratorium Kesehatan Daerah) of Banyuwangi. The results showed that the wash water contained Gram-negative bacteria characterized by round morphology and a pinkish-purple color. The identified bacteria were Escherichia coli and Salmonella spp. The SSA medium exhibited a total of 576 bacterial colonies, indicating a high level of contamination. Factors contributing to bacterial growth included repeated use of the wash water, residues of oily food, and poor sanitation practices. These findings highlight the importance of improving hygiene practices to reduce the risk of disease transmission through contaminated wash water.